Secret Agent Jack Stalwart. [book 7], The Puzzle of the Missing Panda: China - Singer Hunt, Elizabeth (Red Fox, 2006)
Deep inside China's famous Wolong Nature Reserve, an endangered Giant Panda named Ling has disappeared, and for his seventh mission, Jack is paired with a surly, sixteen-year-old park assistant named Fong to help track the panda down. As a member of the evil Scorpion Gang, Fong and a partner Wong have been posing as assistants to steal Ling, and several other rare creatures from the reserve to sell on the black market. Now Jack must infiltrate the ruthless gang's Beijing headquarters, overrun with menacing teenage thieves, and rescue Ling and the other animals before they, and maybe Jack, disappear forever.